Long-term prognostic value of trimethylamine N-oxide in community-based adults and patients with coronary heart disease. (3rd October 2022) - Bjornestad, E; Dhar, I; Svingen, G F T; Pedersen, E R; Orn, S; Svenningsson, M; Tell, G S; Ueland, P M; Sulo, G; Laaksonen, R; Nygaard, O
Abstract: Background: Trimethylamine N-oxide (TMAO) is an amine oxide generated by gut microbial metabolism. Emerging evidence suggests pro-atherosclerotic and pro-inflammatory properties of TMAO; however, the clinical utility of circulating TMAO in risk stratification is uncertain. Purpose: We prospectively assessed relationships of plasma TMAO with long-term risk of all-cause, cardiovascular (CV) and non-CV mortality in community-dwelling adults and patients with coronary heart disease. Methods: By Cox modelling, risk-associations were examined in the Hordaland Health Study (HUSK; 6393 community-based adults) and the Western Norway Coronary Angiography Cohort (WECAC; 4132 patients with suspected chronic coronary syndrome). Results: Median follow-up time was 11.0 and 10.3 years in HUSK and WECAC, respectively. Following adjustments for established CV risk factors in HUSK, the HRs (95% CIs) comparing the 4th vs. 1st TMAO-quartile were 1.11 (0.88–1.40), 0.97 (0.65–1.46) and 1.17 (0.88–1.54) for all-cause, CV and non-CV mortality, respectively. Corresponding risk estimates in WECAC were 1.07 (0.86–1.32), 1.16 (0.83–1.62) and 1.02 (0.77–1.34). Similar results were observed in patients with angiographically significant coronary artery disease and patients with reduced left ventricular ejection fraction. Conclusion: Plasma TMAO was not predictive of long-term all-cause, CV or non-CV mortality in patients with or without established coronary heart disease. This large-scale study does not support a role of TMAO for patient risk stratification in primary or secondary prevention. Funding Acknowledgement: Type of funding sources: None.